Progesterone Sharpens Temporal Response Profiles of Sensory Cortical Neurons in Animals Exposed to Traumatic Brain Injury. Issue 7 (July 2017) - Allitt, Benjamin J.; Johnstone, Victoria P. A.; Richards, Katrina L.; Yan, Edwin B.; Rajan, Ramesh
Traumatic brain injury (TBI) initiates a cascade of pathophysiological changes that are both complex and difficult to treat. Progesterone (P4) is a neuroprotective treatment option that has shown excellent preclinical benefits in the treatment of TBI, but these benefits have not translated well in the clinic. We have previously shown that P4 exacerbates the already hypoactive upper cortical responses in the short-term post-TBI and does not reduce upper cortical hyperactivity in the long term, and we concluded that there is no tangible benefit to sensory cortex firing strength. Here we examined the effects of P4 treatment on temporal coding resolution in the rodent sensory cortex in both the short term (4 d) and long term (8 wk) following impact-acceleration–induced TBI. We show that in the short-term postinjury, TBI has no effect on sensory cortex temporal resolution and that P4 also sharpens the response profile in all cortical layers in the uninjured brain and all layers other than layer 2 (L2) in the injured brain. In the long term, TBI broadens the response profile in all cortical layers despite firing rate hyperactivity being localized to upper cortical layers and P4 sharpens the response profile in TBI animals in all layers other than L2 and has no long-term effect in the sham brain. These results indicate that P4 has long-term effects on sensory coding that may translate to beneficial perceptual outcomes. The effects seen here, combined with previous beneficial preclinical data, emphasize that P4 is still a potential treatment option in ameliorating TBI-induced disorders.